Vocational Education in Correctional Institutions. A Report Based on Four National Hearings - National Advisory Council on Vocational Education, Washington, DC.; National Advisory Council on Vocational Education, Washington, DC.; National Inst. of Education (ED), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Four hearings were held during 1979 by the National Advisory Council on Vocational Education (NACVE) to determine the status of vocational education in correctional institutions. Testimony from 106 witnesses from 27 states led to the overall conclusion that the current level and quality of correctional vocational education is not adequate to provide, on a regular basis, comprehensive vocational education programs to offenders. Over the course of the four hearings, four major issues were implicated in all the problems, frustrations, and possible solutions discussed by witnesses. These issues are the following: (1) funding is inadequate, and there is lack of funding cooperation between state education and correctional agencies; (2) in the area of administration, recruitment, training, and retention of qualified vocational instructors is insufficient; facilities and equipment are inadequate; and there is a lack of coordination and integration of vocational programs with prison industries; (3) regarding comprehensive programming, vocational program standards are lacking and programs are not relevant to realistic job opportunities; and (4) concerning federal policy and leadership, overall coordination is absent; and there is a shortage of research, evaluation, data collection, and technical assistance. (KC)
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Correctional Education; Correctional Institutions; Correctional Rehabilitation; Educational Finance; Educational Needs; Federal Legislation; Federal Programs; Federal Regulation; Federal State Relationship; Hearings; Outcomes of Education; Postsecondary Education; Program Effectiveness; Program Improvement; Rehabilitation Programs; State Agencies; State Departments of Education; State Government; State Programs; Statewide Planning; Vocational Education; Vocational Rehabilitation; National Advisory Council on Vocational Education; Information Analyses; Opinion Papers